Prognosis of clear cell renal cell carcinoma patients stratified by age: A research relied on SEER database - Liao, Zhouning; Wang, Dang; Song, Ning; Xu, Yang; Ge, Heming; Peng, Zhangzhe (Frontiers in Oncology, 2022)
Objective: Clear cell renal cell carcinoma may affect patients of any age. To date, there are only a limited number of large data studies on renal clear cell carcinoma in different age groups. This study assessed CCRCC risk factors in different age groups using the Surveillance Epidemiology and End Results (SEER) database. Methods: We selected 58372 cases from the SEER database. These patients were divided into seven different age groups. Cox regression models were used to find independent risk factors for the survival of CCRCC patients. Based on independent risk factors, a nomogram was drawn with R software. Kaplan-Meier method for survival analysis and X-tile software were used to find the optimal age group for diagnosis. Results: Univariate analysis revealed that patients' age, sex, race, marital status, grade, TNM (tumour, node, metastasis) stage, surgery, WHO/ISUP grade were correlated with survival (P<0.01). Age was an independent risk factor for survival in patients with CCRCC according to multivariate Cox regression analysis (p<0.01). All-cause mortality and tumor-specific mortality increased according to the increasing age of the patients. The optimal cut-off values for age were defined as 58 and 76 years and 51 and 76 years, respectively, according to overall survival (OS) and cause-specific survival (CSS). Conclusion: There is a negative correlation between age and survival of CCRCC patients. The difference in prognosis of patients in different age groups has important implications for clinical treatment. Therefore, the diagnosis and treatment plan should be based on more detailed age grouping, which is more beneficial to improving the prognosis and survival of patients.